When not to design, build, or deploy - Barocas, Solon; Biega, Asia J.; Fish, Benjamin; Niklas, Jędrzej; Stark, Luke (2020 Conference on Fairness, Accountability, and Transparency (FAT* '20), 2020)
Recent debate within the FAT* community has focused on how the field conceptualizes the problems it seeks to address, what approach the field should take in attempting to address these problems, and whether the field should even pursue some of the proposed remedies. Questions regarding when not to design, build, or deploy a technology are perhaps the most common expression of this trend. Identifying the problems to address is inextricably linked to the broader question of how to collectively make decisions about what technologies our societies need and want.